2020
DOI: 10.1161/hypertensionaha.119.13887
|View full text |Cite
|
Sign up to set email alerts
|

Report of the National Heart, Lung, and Blood Institute Working Group on Hypertension

Abstract: The National Heart, Lung, and Blood Institute convened a multidisciplinary working group of hypertension researchers on December 6 to 7, 2018, in Bethesda, MD, to share current scientific knowledge in hypertension and to identify barriers to translation of basic into clinical science/trials and implementation of clinical science into clinical care of patients with hypertension. The goals of the working group were (1) to provide an overview of recent discoveries that may be ready for testing in preclinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 112 publications
0
26
0
Order By: Relevance
“…Intervention Trial) data showed that intensively controlled blood pressure could significantly reduce mortality and CVD events [3]. There has been a report of the National Heart, Lung, and Blood Institute Working Group on Hypertension [4]. can reduce cardiovascular mortality [5].…”
Section: Results Of the Sprint (Systolic Blood Pressurementioning
confidence: 99%
“…Intervention Trial) data showed that intensively controlled blood pressure could significantly reduce mortality and CVD events [3]. There has been a report of the National Heart, Lung, and Blood Institute Working Group on Hypertension [4]. can reduce cardiovascular mortality [5].…”
Section: Results Of the Sprint (Systolic Blood Pressurementioning
confidence: 99%
“…1 A component of the hypertension trend can be assigned to lifestyle trends including consumption of higher sodium/lower potassium diets suggesting that reducing these trends could reduce the incidence of hypertension. [1][2][3][4] For these reasons, definition of molecular mechanisms connecting dietary electrolyte consumption to blood pressure are essential. Pre-clinical studies varying electrolyte intake in rodents utilize synthetic casein-based chows in which the composition (e.g.…”
Section: Key Pointsmentioning
confidence: 99%
“…We want to introduce briefly the two most common inducible models as they form the basis for the largest part of the studies, which are cited in this review. Detailed overviews over all the existing genetic and inducible animal models including their advantages, disadvantages, and translation to human hypertension can be found elsewhere [6][7][8].…”
Section: Murine Models Of Arterial Hypertensionmentioning
confidence: 99%